2001
DOI: 10.1080/j006v20n04_04
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Trends and Practice Strategies in Pediatric Occupational and Physical Therapy

Abstract: This paper identifies and reflects on recent trends in pediatric occupational therapy and physical therapy practice. These trends were initially identified by the student authors for a Maternal and Child Health (MCH) leadership seminar, which was conducted as part of the postprofessional graduate program in physical therapy at the University of Washington. Trends were then reviewed and discussed among the student and faculty authors. Consensus was reached on the most important trends, which were subsequently s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Occupational therapists are trained at the university undergraduate and entry-level Masters level, where professional educational curricula provide the fundamental theoretical and clinical skill basis for future practice ( Jirikowic et al 2001;Wood et al 2001). Through exposure to various theoretical models, occupational therapists build their own personal conceptual frameworks that assist them to integrate theory with practice (Kortman, 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Occupational therapists are trained at the university undergraduate and entry-level Masters level, where professional educational curricula provide the fundamental theoretical and clinical skill basis for future practice ( Jirikowic et al 2001;Wood et al 2001). Through exposure to various theoretical models, occupational therapists build their own personal conceptual frameworks that assist them to integrate theory with practice (Kortman, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Occupational therapists are trained at the university undergraduate and entry‐level Masters level, where professional educational curricula provide the fundamental theoretical and clinical skill basis for future practice (Jirikowic et al 2001; Wood et al . 2001).…”
Section: Introductionmentioning
confidence: 99%
“…On a day-to-day basis, therapists must be aware of research and treatment options, advances in equipment and changing practice models. Often confronted with both limited resources and technical assistance, it has been found that therapists rely heavily on their own experience, and the expert opinion and advice of their colleagues, when making clinical decisions (Bennett et al, 2003;Jirikowic et al, 2001). List serves, such as Paediatricots, provide therapists with access to relevant and immediate communication with colleagues (Schloman, 2001).…”
Section: List Serves and Occupational Therapymentioning
confidence: 99%
“…Occupational therapists advocate with/for people with disabilities. Most often, discussion about advocacy occurs in relation to working with specific groups, such as children (Cahill and Suarez-Balcazar, 2009;Jirikowic et al, 2001;Rigby and Huggins, 2003;Sharp et al, 2012), adults with mental illness (Cogan, 2014;Dressler and MacRae, 1998;Kubina, 2000) and older adults (Andonian and MacRae, 2011;Du Toit et al, 2014;Hart, 2010;Hobson, 2006). Advocacy is also discussed with respect to particularly marginalized groups such as individuals experiencing domestic violence and/or homelessness (Cage, 2007;Grandisson et al, 2009;Gutman et al, 2004;Koch, 2001).…”
Section: Introductionmentioning
confidence: 99%